What's All This Furor About an Enchanted Loom? - Forbes, Raymond (Advances in Social Sciences Research Journal, 2021)
This article explores the gowing interconnections between the brain sciences and the social sciences, It porvides a brief historical summary of the development of brain science, reviews advances in what is currently known about the brain, and dfdescribes where the field stands today. Importantly for those interested in the social sciences, the article also discusses the potential impact of the brain sciences on work in the discipline, indicates why we should care about developments in the brain science field, and provides some practical tools that have come out of the resrarxh, The article concludes with a summary of what the developments might mean for a social sciences practitioner.